NEED ANALYSIS OF CURRICULUM FOR DEVELOPMENT OF PHYSICS LEARNING GAMES CONTAINED WITH SCIENTIFIC LITERATURE - Farhannisa Tsalatsiyah; Hidayati Hidayati (PILLAR OF PHYSICS EDUCATION, 2022)
Education in the twenty-first century is significant because it is intended to improve the quality of human resources. Curriculum becomes an expectation in this situation, and it is poured into the shape of instructional plans or programs implemented by educators in schools. A number of factors contribute to low student learning results in Physics classes, one of which is the curriculum. Learning objectives are less likely to be met when a curriculum is dense. A curriculum analysis can be used to discover the best answer to this situation. The goal of this research was to examine the high school curriculum in order to create physics learning games that included scientific literacy.This was a descriptive research project utilizing a qualitative approach. The participants in this study were all students from Padang high schools. The Stratified Random Sampling Technique was applied also as sampling technique. The sample was chosen based on school accreditation and the Physics UN Score for the 2018/2019 academic year at Padang City High School. In this study, the sample comprised of five institutions: three public high schools and two private high schools. The investigation was conducted by reviewing RPP Physics Class X MIPA SMA records from semesters 1 and 2.Measurement, Vector, Straight Motion, Parabolic Motion, Circular Motion, Newton's Laws, Law of Gravity, Work and Energy, Momentum and Impulse, and Simple Harmonic Vibration make up the current percentage of lesson plans from three high schools. Simple Harmonic Vibration Material has the highest average RPP %, whereas Straight Motion Material has the lowest average RPP percentage. Because the study of RPP papers yielded a low proportion, it can be determined that the Straight Motion Material is a learning game media.